PENGARUH PEMANFAATAN MEDIA PEMBELAJARAN ZOOM MEETING TERHADAP MOTIVASI BELAJAR PESERTA DIDIK DI SMA NEGERI 4 BEKASI - Arman Arman; Amri Dunan (Nusantara Hasana Journal, 2022)
The COVID-19 pandemic resulted in learning being carried out by maintaining a distance which was then called distance learning or PJJ. To carry out PJJ, of course, learning media is needed so that learning can run as expected. Various kinds of learning media are commonly used for PPJ, but in general at SMAN 4 Bekasi the application used is zoom meeting. This study aims to determine the effect of the zoom meeting on the learning motivation of students in informatics subjects in class x. The research method used is quantitative method, using a positivistic paradigm with data analysis using simple correlation techniques and regression analysis. The theory used in this research is the uses and gratifications communication theory. The results showed that the t-count value on the use of zoom meetings on learning motivation was 8.746 > 2.00 with a significance of 0.000 < 0.05. The calculated t value on learning motivation on learning outcomes 2, 656 > 2.00 with a significance of 0.01 < 0.05. it means that H0 is rejected and H1 is accepted, where there is an effect of using zoom meeting learning media on motivation learning of students in class x on informatics subjects, Informatics learning motivation is formed quite well by the zoom meeting.